Robin Williams design workshop - Williams, Robin 1953- (Peachpit Press, 2006)
Learn design theory and practical know-how from the award-winning author/design team, Robin Williams and John Tollett! Robin Williams introduced design and typographic principles to legions of readers with her best-selling Non-Designer's book series. Now she and designer/co-author John Tollett take you to the next level of creative design with practical advice and lessons in composition, visual impact, and design challenges. Presented in Robin and John's signature style-writing that is so crystal clear, it's accessible to absolutely anyone-and illustrated with hundreds of full-color design examples, the ideas in this book tackle design theory, visual puns, and layout and graphics strategies for real-world projects. Developing designers will appreciate the authors' imaginative approach and well-chosen examples. Discover practical and effective design principles and concepts-and how to apply them to virtually any project. Learn why some designs are attention-getting and others are not. Learn how to choose just the right look-corporate or casual, classic or trendy-for specific types of projects, such as business cards, letterhead and envelopes, newsletters and brochures, logos, advertising, and more. Test your design acumen by comparing before-and-after examples. Find a wealth of inspiration for your own design projects. Gain insight into the design process by studying the work of guest designers, who offer their personal commentary and insights.
Print version record
Keywords: Typesetting; Web publishing; Graphic design (Typography); Composition (Industries graphiques); Édition sur le Web; Arts graphiques